Prepositional entries in English-Polish dictionaries - Adamska-Sałaciak, Arleta (Adam Mickiewicz University, 2008)
The present paper examines the microstructure of entries devoted to prepositions in bilingual English-Polish dictionaries. Given the problems inherent in the lexicographic treatment of function words, it seems worthwhile to ask: – what are the strategies employed in cases of lack of interlingual equivalence? – what is the preferred type of sense-structure (i.e. source-language based, target-language based or mixed)? – does the entry highlight links between related senses? – how much phraseology is deemed necessary to present the properties of the preposition in question? – how does the choice of entry organisation affect its usefulness and user-friendliness? – what possible improvements could be introduced? Answers to the above questions are believed to have implications for lexicography in general, not merely bilingual lexicography in the English-Polish context.